ISO 26000 : the business guide to the new standard on social responsibility - Moratis, L. T. (Lars T.) (ISO 26000, 2011)
Over the last ten years, Corporate Social Responsibility (CSR) has grown from being criticised as a management fad to being endorsed as good business practice by the majority of the worlds leading companies. ISO, the International Organization for Standardization, began developing an International Standard providing guidelines for social responsibility (SR) in 2005. This long-awaited guidance standard was published in 2010 as ISO 26000. Developed by stakeholders from industry, government, labour, consumers, non-governmental organizations and others, ISO 26000 has become the single most authoritative worldwide standard for SR. This book covers all the key content of ISO 26000, examining the development of the standard, the topics covered and how key themes such as stakeholders are dealt with. It is rich in tools and benchmarking exercises, illustrative material, case examples, and interviews with companies looking to base their CSR policy on ISO 26000. It also contains an overview of the actions and expectations of organizations that wish to work in accordance with ISO 26000.